Learner performance in integrated science process skills and attitudes in hands-on practical work versus virtual practical work - Ndoro, Mugove Chawapiwa (School of Education, 2018)
This research study was conducted in an urban high school in Western Cape province of South Africa. The research study investigated the effect of virtual practical work on learner performance in science process skills and attitude, working with a non-random sample group of grade 10 physical sciences learners. In this experimental design research, the treatment group of 22 learners was taught the concept of 'phase change in matter' through virtual practical work. On the other hand, the control group was taught the same concept through hands-on practical. A pre- and post-test instrument of 30 multiple choice items on integrated science process skills was used to measure learners' performance. The test scores were statistically analysed using Quickcalcs, to compare the overall learner performance in the two groups, and also to compare learner performance in different categories of science process skills. A 12-item questionnaire was designed to test the learner s' attitude towards virtual and hands-on practical. The statistical t test analysis on the average scores indicated insignificant difference between the performance of the two groups, with a p value greater than 0,05. When learners' performance in different process skills categories were compared, t test scores revealed significant differences in some categories and non-significant differences in some categories. The questionnaire results indicated that the learners' attitude was biased towards hands-on practical work. The significance of this research study is that virtual practical can be used to develop some science process skills.